Comparison job satisfaction between occupational therapists and speech therapists in Karaj - Abbas Rahimi Foroushani; Homa Nasseh (Vesnu Publications, 2013)
Abstract   Introduction: Job satisfaction considered asan important factor in increasing productivity, Workers belonging and attachment to the work environment and improving the quantity andquality of work. Therefore this factor is important in various careers. Materials and Methods: This is a descriptive-analytic study.It was done between Occupational therapists and speech therapists in the Karaj. In each group 16 individuals were randomly collected demographic and job satisfaction (JDI) questionnaires completed. Reliability and validity of questionnaire was approved by similar internal articles.Data analyzing has done by nonparametric tests and SPSS software. Results: Scores for job satisfaction in occupational therapists (76/0 ± 31/3) were higher than the speech therapists (45/0 ± 80/2. In Speech therapists group between job satisfaction with supervision, salary and promotion was a significant correlation. In occupational therapist be found a significant relationship between job satisfaction with nature of job, salary, promotion and colleagues. Conclusion: Scores in both groups indicates that corrective actions are necessary. Actions for increase job security, improved ergonomics, workplace conditions, career development and job enrichment can help to increase job satisfaction in these two groups. Keywords:Speech therapist, Occupational therapists, Job satisfaction, Karaj, Rehabilitation, JDI questionnaire